Attenuation of gadolinium enhancement in pituitary gland on magnetic resonance imaging of patients with pediatric growth hormone deficiency - Mariko Doai; Yuka Nishino; Yasuhiko Hayashi; Masatsune Ito; Munetaka Matoba (BMC Medical Imaging, 2023)
Abstract Background Although it is generally thought that disturbance of perfusion in the anterior lobe of the pituitary gland leads to complete or partial hypopituitarism, the gadolinium (Gd) enhancement findings on Magnetic Resonance Imaging (MRI) of patients with growth hormone deficiency (GHD) remain unknown. The purpose of this study was to compare Gd enhancement of the pituitary gland on MRI of patients with GHD to that of healthy subjects. Methods In this retrospective study, we analyzed the data of 10 patients with clinically diagnosed GHD who underwent Gd-enhanced MRI of their pituitaries (age 8.3 $$±$$ 3.5 year, female 1, males 9), together with data of 5 patients with clinically normal growth hormone (GH) dynamics who also underwent Gd-enhanced pituitary MRI (age 6.2 $$±$$ 3.4 year, female 4, males 1). In each subject, a maximum-diameter region of interest (ROI) was drawn on the anterior pituitary gland of post Gd-enhanced coronal T1-weighted images, and the signal intensity ratio of the anterior pituitary gland to the white matter on the right temporal lobe of the same cross section was assessed. Results The mean area of the ROI in the anterior pituitary gland and white matter of temporal lobe on the same cross section showed no significant differences between patients with GHD and those with normal GH (pituitary, 17.43 mm2 $$±$$ 8.24 vs. 21.08 mm2 $$±$$ 10.40, p = 1.00; white matter, 74.47mm2 $$±$$ 24.19 and 62.50 mm2 $$±$$ 17.90, p = 0.37), suggesting that the sizes of the pituitary glands were comparable. The ratios of Gd enhancement in the anterior pituitary gland showed significant differences between GHD and normal-GH subjects ( $$±$$ $$0.716±$$ 0.68 $$±$$ 0.26 vs. $$0.72±$$ 0.16, p= 0.04). Conclusions These results suggested that the contrast effect on Gd-enhanced MRI is attenuated in the pituitary glands of patients with GHD compared to those with normal GH. These new clinical findings regarding Gd-enhanced MRI can assist the diagnosis of pediatric GHD.